2018
DOI: 10.1021/acs.iecr.8b01139
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline Based Materials as a Method to Eliminate Haloanisoles in Spirits Beverages

Abstract: In this research, the abilities of two polyanilinebased materials (PANI-EB and PANI-ES) were evaluated as potential fining agents to eliminate 2,4,6-trichloroanisole (TCA) and 2,4,6-tribromoanisole (TBA). The results showed that the retention percentages of TCA and TBA were higher than 68% for all the materials tested in methanol, and they vary according to the interaction time and the quantity of polymer used. The polymers were also tested in whisky following the same procedures and considering the results ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Valdes et al [ 23 ] also showed that the application of two polyaniline-based materials (0.1 to 0.5 g/L) to wine contaminated with TCA and TBA (20 ng/L) had TCA and TBA removal percentages of 68–72%, and 84–85%, respectively. A recent study of the application of plastic film to wines stored in wooden barrels with 3 ng/L and 9 ng/L of TCA contamination showed that immersion of plastic film in wine for 8 h reduced the TCA concentration by 47% to 57%, and that after 24 h the TCA reductions were 73% and 75%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Valdes et al [ 23 ] also showed that the application of two polyaniline-based materials (0.1 to 0.5 g/L) to wine contaminated with TCA and TBA (20 ng/L) had TCA and TBA removal percentages of 68–72%, and 84–85%, respectively. A recent study of the application of plastic film to wines stored in wooden barrels with 3 ng/L and 9 ng/L of TCA contamination showed that immersion of plastic film in wine for 8 h reduced the TCA concentration by 47% to 57%, and that after 24 h the TCA reductions were 73% and 75%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, according to the results of this study, it can be observed that, globally, the use of plastic film to eliminate/reduce the content of haloanisols in wines did not impact the content of phenolic compounds (proanthocyanidins and anthocyanins) for up to 24 h of treatment with the film [ 22 ]. Valdés et al [ 23 ] also studied the possibility of applying two polyaniline-based materials (100 to 500 mg/L) to remove TCA and TBA in methanol at a concentration of 20 ng/L. The results of these authors showed that the removal percentages of TCA and TBA were 68–72% and 84–85%, respectively, for the two materials tested in methanol, and their effectiveness varied with the interaction time and with the amount of polymer used.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that some polymers (polyanilines) were able to eliminate 75% of TCA and 13% TBA in whisky without significative consequences on the aromatic profile and on the total phenolic content [66]. The same team also verified the possibility to use these inexpensive polymeric materials as potential fining agents for elimination of TCA in the beverage industry, through a hybrid strategy of computational and experimental studies [67].…”
Section: Curementioning
confidence: 90%
“…It is known that the drying step eliminates many volatile compounds, alcoholic compounds (such as ethanol and methanol), and other compounds present in low concentration (Aru et al ). In spite of this, our group recently published a study using the same methodology in whisky (Valdés et al ), which demonstrated that the main volatile compounds and total phenolic content of alcoholic samples did not change significantly. We assume, therefore, that the drying step does not affect its sensory properties.…”
Section: Methodsmentioning
confidence: 99%